2011
DOI: 10.3727/096504012x13340632812677
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Is Critical for the Proliferation, Invasiveness, and Drug Resistance of Human Tongue Carcinoma Cells

Abstract: PIK3CA is an oncogene component of phosphatidylinositol 3-kinase (PI3K) signaling pathway and is associated with cell proliferation and carcinogenesis in a variety of human cancers. PIK3CA mutation is correlated with the aggressiveness of many epithelial cancers. And so PIK3CA is considered as a major oncogene in many human epithelial malignancies. However, its role in tongue carcinoma is unknown. We used lentiviral-mediated interfering short hairpin RNAs (shRNAs) to knock down PIK3CA expression in tongue carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In an in vitro study using a tongue cancer cell line, inhibition of PIK3CA expression was shown to suppress PTEN and Akt phosphorylations, resulting in decreased proliferative activity and invasiveness and increased drug sensitivity. 22 In gastric cancer cell lines, knockdown of PIK3CA by siRNA also led to reduced tumor cell invasion and migration, suggesting that PIK3CA expression is involved in cancer cell invasion. 23 In this study, we found that PIK3CA upregulation was associated with tumor cell invasion.…”
Section: Discussionmentioning
confidence: 95%
“…In an in vitro study using a tongue cancer cell line, inhibition of PIK3CA expression was shown to suppress PTEN and Akt phosphorylations, resulting in decreased proliferative activity and invasiveness and increased drug sensitivity. 22 In gastric cancer cell lines, knockdown of PIK3CA by siRNA also led to reduced tumor cell invasion and migration, suggesting that PIK3CA expression is involved in cancer cell invasion. 23 In this study, we found that PIK3CA upregulation was associated with tumor cell invasion.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have revealed that PIK3CA and PTEN have an important role in the occurrence and development of OSCC (23)(24)(25)(26)(27)(28)(29)(30)(31). PIK3CA is the key molecule in the PI3K/AKT signaling pathway (40), while PTEN is the most important negative regulatory component in the PI3K/AKT signaling pathway (41).…”
Section: Per2 Expressionmentioning
confidence: 99%
“…At present, there is no clear opinion regarding the associations between PER2 expression changes and the occurrence, development and survival outcomes of OSCC. It has been shown that the development of OSCC is closely related to expression changes of several important tumor-related genes, such as PIK3CA, PTEN, P53, P14ARF and caspase-8 (28)(29)(30)(31)(32)(33)(34). However, it is unclear whether there is any correlation between PER2 expression and the aberrant expression of these tumor-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenic factors such as VEGF-1 have been shown to activate the PI3K pathway preferably in collaboration with PLCγ to promote cancer progression and migration [144] (Figure 7). The other component of the PI3K signaling pathway is PI3KCA which is correlated with cancer progression and drug resistance in the tongue [145] and breast cancers [146]. In an effort to develop combinatorial therapies to decipher drug resistance, Gupta et al investigated the use of KIT/PI3K/MAPK (KPM) pathways as potential targeted therapy for gastrointestinal stromal tumors (GIST).…”
Section: Personalized Precision Medicine and Combinatorial Therapiesmentioning
confidence: 99%